1997
DOI: 10.1177/027112149701700303
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion and Mainstreaming Revisited---Again Teaching Experience and Specialist Support: A Survey of Preschool Teachers Employed in Programs Accredited by NAEYC

Abstract: A national mail survey of preschool teachers (N = 500, return rate of 55.2%) employed in programs accredited by the National Association for the Education of Young Children was conducted to gain descriptive information about (a) the teachers' preparation and program organization and (b) their experience with children with disabilities, the IEP process, special educators, and other specialists. Results indicated that more than half of the respondents currently had a child with disabilities in their classroom an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 2 publications
1
23
0
Order By: Relevance
“…Recent surveys also indicate that a majority of early childhood programs, including community-based and private programs, report enrolling one or more children with developmental delays or disabilities (Cryer, Hurwitz, & Wolery, 1999;McDonnell, Brownell, & Wolery, 1997;Wolery et al, 1993).…”
Section: Mcdonnell Brownell and Wolerymentioning
confidence: 99%
“…Recent surveys also indicate that a majority of early childhood programs, including community-based and private programs, report enrolling one or more children with developmental delays or disabilities (Cryer, Hurwitz, & Wolery, 1999;McDonnell, Brownell, & Wolery, 1997;Wolery et al, 1993).…”
Section: Mcdonnell Brownell and Wolerymentioning
confidence: 99%
“…Scholars (Guralnick, 2001;Odom et al, 2006) have suggested that the peer group in inclusive settings may provide "more age-appropriate, competent and positive models" (Odom et al, 2006, p. 807) of development than in special education classrooms. Approximately half of preschool children with disabilities receive special education in programs that include typically developing peers (U.S. Department of Education, 2004), and one-third to twothirds of preschool programs designed for typically developing children include at least one child with a disability (Buysse, Wesley, Bryant, & Gardner, 1999;McDonnell, Brownell, & Wolery, 1997). In addition, young children with disabilities participate in Correspondence should be sent to Karen E. Diamond, Department of Child Development and Family Studies, Purdue University, 101 Gates Rd., W. Lafayette, IN 47907-2020.…”
mentioning
confidence: 99%
“…This represented a doubling of children enrolled from just 5 years earlier. In a more recent survey of programs accredited by the National Association of Educators of Young Children (NAEYC), McDonnell, Brownell, and Wolery (1997) found that 58% of these high-quality programs included children with disabilities. However, of the teachers who reported that they currently served a child with disabilities in their classroom, only 25% reported working directly with an early childhood special educator.…”
mentioning
confidence: 99%